“I let down my nets and pulled.” Langston Hughes’ The Big Sea (1940) as a Slave-Narrative Inspired Autobiography - Tarnóc, András (FOCUS: Papers in English Literary and Cultural Studies, 2022)
The aim of the essay is to investigate the connection between the slave narrative and the Harlem Renaissance through Langston Hughes’ The Big Sea (1940). The work recalls Hughes’ personal growth and professional development from a struggle-filled young adulthood to becoming an accomplished literary figure. I consider Hughes’s text a slave narrative-inspired autobiography. In order to substantiate my hypothesis I primarily rely on Frances Smith Foster and Kim Green’s cyclical interpretation of the slave narrative, John Olney’s theory concerning the respective form and content related conventions, and Mikhail Bakhtin’s chronotope model. I identify three formative experiences in Hughes’s life: his extended stay with his father in Mexico at age 19, his voyage to Africa in 1923 and his ”sociological study trip” to the South in 1924. My treatise retraces how the options provided by the genre of autobiography helped Langston Hughes to convert an unwritten self into literary representation.